Reaction of Epoxides. IV. Addition of 2, 3-Epoxypropyl Phenyl Ether to Oximes and Hydrazones - KOJIMA, YOKO; FURUKAWA, MITSURU; SUGITA, MAKOTO; HAYASHI, SEIGORO (Chemical & pharmaceutical bulletin, 1973)
Reaction of 2, 3-epoxypropyl phenyl ether with equivalents of aromatic aldoximes and hydrazones in which the difunctional group, the carbon-nitrogen double bond adjacent to the active hydrogen group, is involved in the molecule was attempted in the presence of Lewis acid catalyst. In the result, the 1 : 1 adduct formed by the addition of the epoxide to the active hydrogen group was obtained as the only product, no trace of any cycloaddition product of the epoxide to the carbon-nitrogen double bond being isolated. The structure of the adduct was also discussed.